Medical Imaging 2022: Image Perception, Observer Performance, and Technology Assessment 2022
DOI: 10.1117/12.2613134
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the limited performance of a deep-learning-based SPECT denoising approach: an observer-study-based characterization

Abstract: Multiple objective assessment of image-quality (OAIQ)-based studies have reported that several deep-learning (DL)-based denoising methods show limited performance on signal-detection tasks. Our goal was to investigate the reasons for this limited performance. To achieve this goal, we conducted a task-based characterization of a DL-based denoising approach for individual signal properties. We conducted this study in the context of evaluating a DL-based approach for denoising single photon-emission computed tomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…For example, a technical efficacy study may observe suboptimal performance of an AI-based denoising algorithm on the tumor-detection task. Then, the evaluation study could investigate the performance of the algorithm for different tumor properties (size/tumor-to-background ratio) on the detection task (66). This will provide insights on the working principles of the algorithm, thus improving the interpretability of the algorithm.…”
Section: Postdeployment Evaluationmentioning
confidence: 99%
“…For example, a technical efficacy study may observe suboptimal performance of an AI-based denoising algorithm on the tumor-detection task. Then, the evaluation study could investigate the performance of the algorithm for different tumor properties (size/tumor-to-background ratio) on the detection task (66). This will provide insights on the working principles of the algorithm, thus improving the interpretability of the algorithm.…”
Section: Postdeployment Evaluationmentioning
confidence: 99%
“…22 Recent work studying the effect of denoising using neural networks on detection performance in single positron emission computed tomography showed that denoising could decrease detection performance even if it improved RMSE and SSIM. 30 In another study using simulated images showed similar results. 31 Exploring applications where regularization helps in a detection-based perspective would be useful to better understand the regimes where metrics like ERMSE and detection performance agree and disagree.…”
Section: Resultsmentioning
confidence: 61%
“…Some slight improvement was seen in the context of ramp-spectrum noise for human observers 17 and in ideal observer performance in undersampled MRI 22 . Recent work studying the effect of denoising using neural networks on detection performance in single positron emission computed tomography showed that denoising could decrease detection performance even if it improved RMSE and SSIM 30 . In another study using simulated images showed similar results 31 .…”
Section: Resultsmentioning
confidence: 81%
“…observed no significant correlation between peak signal‐to‐noise ratio and SSIM values and classification performance for a tumor classification task in chest radiographs 19 . A study by our group observed these limitations with a 2D single photon emission computed tomography (SPECT) system with lumpy background‐based tracer distribution models 21 . While these studies show the limitations of these FoMs, it is unclear if the results from these studies are indicators of performance in clinical settings in nuclear medicine.…”
Section: Introductionmentioning
confidence: 97%